Augmentation of tunnel-air convective heat transfer forced by duct ventilation in a geothermal construction tunnel. (November 2021) - Chen, Qi; Chen, Shougen; Zhang, Heng; Ran, Guangyao; Zhang, Fei; Yang, Haipeng
Abstract: This work conducts numerical simulations and parameter analyses to investigate the augmentation performance of tunnel-air convective heat transfer (CHT) forced by duct ventilation in a dead-end tunnel concerned in tunnel space cooling inside a geothermal construction tunnel. Attributed to duct nozzle jet-flow, the CHT performance varies longitudinally and augments in the region close to duct nozzle, whereas holds a flat trend in the tunnel entrance region far away. In this work, the CHT is represented by surface-averaged Nusselt number ( Nu ) at the tunnel-air interface with a spatial resolution to the tunnel length, and the CHT augmentation region is highlighted by the bulge pattern of the Nu distribution curve. The three-dimensional Computational Fluid Dynamics is based on to simulate the actual CHT concerning both airflow turbulence and near-wall conditions, and the influences of parameters considering different (ⅰ) shapes of tunnel cross-section, (ⅱ) outlet airflow Reynolds number (Re), and (ⅲ) ventilation duct position and (ⅳ) diameter on the CHT augmentation are respectively identified. The results show the CHT augmentation region is less influenced by the shape of tunnel cross-section and Reynolds number but notably affected by ventilation duct diameter and position. A duct with a smaller diameter and position at the tunnel side is optimal to the CHT augmentation, and hence should be considered in the duct ventilation design for tunnel space cooling in a geothermal construction tunnel. Furthermore, a semi-empirical equation about the local Nu-Re correlation for the CHT augmentation region is proposed based on numerical results. Highlights: The augmentation of tunnel-air CHT is highlighted by the Nu distribution curve. The influences of parameters considering various conditions are identified. A semi-empirical equation is proposed to depict the augmentation of tunnel-air CHT.